2020
DOI: 10.30919/esmm5f707
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Compatibility of Fluorine-Acrylic Emulsion and Sulphoaluminate Cement in the Design of Composite Coating: Effects of Sorbitol and Its Mechanism

Abstract: Both fluorine-acrylic (FA) emulsion and sulphoaluminate cement (CSA) have been proved as satisfactory marine engineering materials, and a better performance can be expected by their combined use. However, their compatibility has rarely been researched. In this study, the effects of sorbitol and its mechanism are investigated by the cement paste fluidity, rheological property, tensile strength, water absorption and scanning electron microscopy (SEM) tests. The results showed that, compared with sodium tripolyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The peaks at 1456 and 1384 cm -1 correspond to the vibration bending of -CH3 and -CH2 [29,46]. Further observation found that compared with the spectrum of F0, F4 has wider peaks between 1116 ~ 1158 cm -1 [47], which can be ascribed to the strong absorption of the C-O-C group being overlapped by the stretching vibration of the C-F band [30,[48][49][50].…”
Section: Synthesis and Characterization Of The Resinsmentioning
confidence: 92%
“…The peaks at 1456 and 1384 cm -1 correspond to the vibration bending of -CH3 and -CH2 [29,46]. Further observation found that compared with the spectrum of F0, F4 has wider peaks between 1116 ~ 1158 cm -1 [47], which can be ascribed to the strong absorption of the C-O-C group being overlapped by the stretching vibration of the C-F band [30,[48][49][50].…”
Section: Synthesis and Characterization Of The Resinsmentioning
confidence: 92%
“…The filtrate produced from this reaction is mostly discarded. Zeolites are used in many applications such as improving the hydration properties of cement paste [11], in cements for composite coating designs [12], and removal of pollutant dyes in wastewater [13]. They can also be used as nanocomposites for dye degradation [14], inhibition of antimicrobial activities, and in microalgalimmobilized biocomposites [15].…”
Section: Introductionmentioning
confidence: 99%
“…As for waterproof coatings, they should exhibit great durability during variation of stress for a long time. To prepare films with excellent performance which can balance the contradiction between tensile strength and elongation at the break, the SA polymer to cement ratio (denoted as p / c ) is key to solve this problem (Liang et al , 2020). It can be concluded that the mechanical property of coatings films would be enhanced when the weight of the polymer is equal to cement paste ( p / c = 1) after many attempts.…”
Section: Resultsmentioning
confidence: 99%